2006
DOI: 10.1017/s0031182006001120
|View full text |Cite
|
Sign up to set email alerts
|

Eimeria-parasites are associated with a lowered mother's and offspring's body condition in island and mainland populations of the bank vole

Abstract: This study, based on correlative data, tests the hypothesis that infections with Eimeria spp. parasites exert a significant loss of fitness of bank voles (Clethrionomys glareolus) reflected in lower reproductive success and survival, declining host population densities and are associated positively with population size. The study was conducted in 20 mainland and 27 island populations in central Finland during May-September in 1999. Faecal samples showed that 28% of 767 individuals were infected with Eimeria sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…Although a link between condition and disease is not unexpected (Beldomenico et al 2008), field studies that document this link in wild populations are rare (e.g. Hakkarainen et al 2007;Beldomenico et al 2009). Effects of poor condition and infection can be synergistic, because individuals in poor condition might be less resistant to disease, and infection might further reduce individual condition (Beldomenico et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although a link between condition and disease is not unexpected (Beldomenico et al 2008), field studies that document this link in wild populations are rare (e.g. Hakkarainen et al 2007;Beldomenico et al 2009). Effects of poor condition and infection can be synergistic, because individuals in poor condition might be less resistant to disease, and infection might further reduce individual condition (Beldomenico et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in fecundity in parasitized hosts was reported in several studies of endemic microparasites in wildlife (Phillips 2000; Lello et al 2005;Telfer et al 2005;Hakkarainen et al 2007). Chlamydia pecorum infection, which causes reproductive-tract infections in koalas Phascolarctos cinereus, may limit the reproductive potential of populations (Phillips 2000).…”
Section: Introductionmentioning
confidence: 85%
“…Finally, by decreasing individual body condition, which is generally related to number or body condition of oVspring, parasites decrease oVspring quality and recruitment in infected populations. Hakkarainen et al (2007) demonstrated that the body mass of bank voles was negatively related to the presence of Eimeria spp., an intestinal protozoan frequently documented in rodents (Laakkonen et al 1998). Mothers infected by Eimeria spp.…”
Section: Introductionmentioning
confidence: 99%
“…Parasites can alter host physiology (Schall et al 1982;Simon et al 2004), body condition (Hakkarainen et al 2007;Vandegrift et al 2008;Turner et al 2012), behavior (Schall et al 1982;Goodman and Johnson 2011), social dominance (Schall and Houle 1992;Zohar and Holmes 1998), and life history (Schall 1983;Schall and Dearing 1987;Shields and Wood 1993;Merino and Potti 1995;Lochmiller and Deerenberg 2000;Skarstein et al 2001;Chadwick and Little 2005;Cox and John-Alder 2007;Kallio et al 2007), leading to complex ecological and evolutionary consequences in host populations (Hamilton and Zuk 1982;Buckling and Rainey 2002;Chadwick and Little 2005). Theoretical and field studies suggest that parasites can regulate host populations, playing a role comparable to predators (May and Anderson 1979;Albon et al 2002;Redpath et al 2006;Lemaître et al 2009).…”
Section: Introductionmentioning
confidence: 99%